2022
DOI: 10.1093/nar/gkac251
|View full text |Cite
|
Sign up to set email alerts
|

m6A and YTHDF proteins contribute to the localization of select neuronal mRNAs

Abstract: The transport of mRNAs to distal subcellular compartments is an important component of spatial gene expression control in neurons. However, the mechanisms that control mRNA localization in neurons are not completely understood. Here, we identify the abundant base modification, m6A, as a novel regulator of this process. Transcriptome-wide analysis following genetic loss of m6A reveals hundreds of transcripts that exhibit altered subcellular localization in hippocampal neurons. Additionally, using a reporter sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 121 publications
3
32
0
Order By: Relevance
“…TRIBE-STAMP revealed that the majority of target mRNAs of each DF protein are also bound by the co-expressed DF protein, regardless of the DF protein pair being examined, a finding that we validated by RIP-seq against both tagged and endogenous DF proteins. However, we also identified many mRNA targets that are unique to DF1 compared to DF2 or DF3, which mirrors what we found when we reanalyzed DF iCLIP data from HeLa cells (Patil et al 2016), as well as our previous RIP-seq studies in hippocampal neurons (Flamand and Meyer 2022). Overall, our data demonstrate that TRIBE-STAMP can accurately identify the target RNAs of two RBPs simultaneously in cells and showed that the mRNA targets of all three DF proteins are largely shared at the gene level.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…TRIBE-STAMP revealed that the majority of target mRNAs of each DF protein are also bound by the co-expressed DF protein, regardless of the DF protein pair being examined, a finding that we validated by RIP-seq against both tagged and endogenous DF proteins. However, we also identified many mRNA targets that are unique to DF1 compared to DF2 or DF3, which mirrors what we found when we reanalyzed DF iCLIP data from HeLa cells (Patil et al 2016), as well as our previous RIP-seq studies in hippocampal neurons (Flamand and Meyer 2022). Overall, our data demonstrate that TRIBE-STAMP can accurately identify the target RNAs of two RBPs simultaneously in cells and showed that the mRNA targets of all three DF proteins are largely shared at the gene level.…”
Section: Discussionsupporting
confidence: 82%
“…We performed RNA-seq on cells co-expressing the ADAR and APOBEC1 fusion proteins for a particular DF protein. To identify A2I and C2U editing events transcriptome-wide, we developed a modified version of Bullseye, a pipeline we previously created to identify C2U editing events introduced by the m 6 A profiling method DART-seq(Meyer 2019; Flamand and Meyer 2022; Tegowski et al 2022). Briefly, we optimized Bullseye for detection of both A2I and C2U mutations that are enriched relative to reference samples expressing the ADAR or APOBEC1 proteins alone.…”
Section: Resultsmentioning
confidence: 99%
“…Among these proteins are the YT521-B homology (YTH) domain family proteins, which contain a highly conserved YTH domain that specifically recognizes m 6 A. Several RNA processing events are impacted by m 6 A, including miRNA biogenesis, pre-mRNA splicing, polyadenylation, cellular localization, mRNA stability, and translation [ 49 ], and reader proteins are the primary mediators of these diverse effects [ 36 , 50 ]. In addition, m 6 A-dependent changes in RNA structure can influence gene expression through the control of translation or through impacting RNA:protein interactions [ 51 ].…”
Section: Rna Base Modificationsmentioning
confidence: 99%
“…YTHDC1 is important for germ cell development and contributes to mRNA abundance and translation regulation [51,80,81]. The "DF" proteins YTHDF1, 2, and 3 are a major family of cytoplasmic m 6 A readers and have been implicated in the regulation of mRNA stability, translation, and localization [49,[82][83][84][85]. A longstanding model for these proteins has been that they have unique functions, with DF2 primarily promoting mRNA degradation, DF1 promoting translation, and DF3 contributing to both degradation and translation.…”
Section: Boxmentioning
confidence: 99%
“…N6-methyladenosine (m 6 A) RNA methylation is the most common conserved internal transcriptional and modification epigenetic modification. m 6 A is a dynamic process, and three kinds of essential regulators (known as “writer”, “eraser”, and “reader”) are involved in the regulation of this modification process in the human body, leading to several facets changes in RNA processing, including RNA stability, alternative splicing and translation 4 11 . As a hot spot in epigenetic research in recent years, the fundamental role of m 6 A in cancer development and prognosis may help us clarify the mechanism of CC with a novel perspective.…”
Section: Introductionmentioning
confidence: 99%